2017
DOI: 10.5530/jcdr.2017.4.32
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic Syndrome among Apparently Healthy Nigerians with the Harmonized Criteria: Prevalence and Concordance with the International Diabetes Federation (IDF) and Third Report of the National Cholesterol Education Programme - Adult Treatment Panel III (NCEP-ATP III) Criteria

Abstract: Background:The prevalence of metabolic syndrome varies by the definition used and the population studied. In order to make comparison among various studies possible, a new criterion which harmonizes the previous definitions was proposed. This study aims to determine the prevalence of metabolic syndrome with the harmonized criteria, and its concordance with the International Diabetes Federation (IDF), and National Cholesterol Education Programme-Adult Treatment Panel (NCEP-ATP III) criteria. Methods: One hundre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
5

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 33 publications
1
6
5
Order By: Relevance
“…The zero prevalence of low HDL observed in this study irrespective of age, gender, and occupation is in contrast with 68.6%25 found among apparently healthy adults in Sagamu and Remo North LGAs of Ogun State, Nigeria, and 23.2% among working adults in Ethiopia 26. There is apparently no reason for this zero prevalence since the consumption of fluids other than water is high, and most of these fluids contain added sugar.…”
Section: Discussioncontrasting
confidence: 80%
“…The zero prevalence of low HDL observed in this study irrespective of age, gender, and occupation is in contrast with 68.6%25 found among apparently healthy adults in Sagamu and Remo North LGAs of Ogun State, Nigeria, and 23.2% among working adults in Ethiopia 26. There is apparently no reason for this zero prevalence since the consumption of fluids other than water is high, and most of these fluids contain added sugar.…”
Section: Discussioncontrasting
confidence: 80%
“…24 Among type-2 diabetes patients, documented prevalence of metabolic syndrome was higher ranging between 59.1%-87.1% [34][35][36][37][38] with a range between 24.7%-40.7% amongst hypertensive patients, [19][20][21][22][23][24] however with different diagnostic criteria utilized. 39 Likewise, a recent community-based study done in the urban city of Sokoto, North-West Nigeria reported a similar high prevalence of metabolic syndrome of 35.1%, 20 consistent with previous reports by Akintunde et al amongst hypertensive Nigerians in the South-West Nigeria 21 as well as 31.2% overall prevalence documented in South-East Nigeria increased to 40.4% with 2 risk factor clusters. 23 Some other study on CMRFC in 11 semi-urban communities in Ekiti and Osun States of South-Western Nigeria documented a prevalence of 32.9% and 8% of two and at least three cardiovascular risk factors respectively.…”
Section: Discussionsupporting
confidence: 84%
“…Larger community or population based studies involving lipid profile, insulin resistance and CRP should be carried out across the Northern part of the country and by extension other geo-political zones to determine the impact of the CMRFC on a larger scale as this study may be limited by this even though similar studies with such numbers or smaller numbers made valid conclusions. 21,22,25,39,44,50 lifestyle differences, varied degrees of urbanization and sociocultural disparity may account for the marked differences in different studies. 60 The use of diuretics especially the thiazides which was found in more than half of the study population (48.3% in combination therapy and 15.6% as a single agent) may have contributed to the higher prevalence of prediabetes and diabetes as diuretics have been shown to affect glucose homeostasis.…”
Section: Limitationsmentioning
confidence: 99%
“… 1 These criteria have good concordance with the International Diabetes Federation definition, thus making comparisons among studies possible. 17 …”
Section: Methodsmentioning
confidence: 99%